Improving the Use of Materials Used in Road Paving in Desert Areas A Descriptive and Analytical Study: Southern Libya (Al-Farooq Journal of Sciences, 2026)
This study aimed to improve the properties of road paving in desert areas using plastic waste (polyethylene). The research adopted the descriptive analytical approach. An electronic questionnaire was distributed to a sample of specialists. The results showed that recycling these materials reduces costs, improves the mechanical properties of the asphalt mixture, and achieves environmental benefits.